Bibliometric Analysis on Scholarly Journals of PVA Hydrogel Membrane Using VOSviewers Software - Virni Grace Irene Damanik; Asep Bayu Dani Nandiyanto (Universitas Negeri Medan, 2023)
The development of technology in this world is already developing rapidly. One of the advanced technologies that support research planning is bibliometrics. This study aims to analyze the scope of research on PVA Hydrogel Membrane using VOSviewer using bibliometric review with a mapping process to ensure that the research to be carried out has never been studied and knows the relationship of each related item. The three processes underlying the search use the keywords